Impaired Modulation of Pain in Patients with Postherpetic Neuralgia - Gisèle Pickering; Bruno Pereira; Elodie Dufour; Sylvie Soule; Claude Dubray (Pain Research and Management)
BACKGROUND: The efficiency of inhibitory pain descending pathways (evaluated using conditioned pain modulation [CPM]) has not been studied in postherpetic neuralgia (PHN).